Comparative analysis of numerical systems and comprehensive systems in dental professional education: Analisis perbandingan numerical system dan comprehensive system pada pendidikan profesi kedokteran gigi - Mansjur Nasir; Rezki Ulwan Sudarmin; Karima Qurnia Mansjur; Zilal Islamy Paramma (Makassar Dental Journal, 2024)
It is currently considered the best way to achieve better oral health. The numerical requirement teaching model focuses on the treatment of predefined cases that students must perform to fulfil the requirements for examinations. There is now a different sys-tem that can challenge students to adopt a philosophy of care known as the comprehensive system. Comprehensive dental care is the fulfilment of accumulated dental care needs. This review discusses the dental profession clinical curriculum system and to compare the comprehensive system and numerical requirement system with literature review. It was concluded that the compre-hensive treatment programme provides students with a broader education and improves the efficiency and quality of patient care. The numerical requirement system is considered an important tool in dental education to ensure that students receive experi-ence while completing a predetermined system of requirements.